(3GdLGeY deaQOGJ GdCOhjI hGdGZPjIs - (3YHO Gddg Hf CMeO GdeGdbj, VjGA GdOjf, GHf GdHjWGQ , J (B646 (3g` s
(3ChdgG (B:s
(3JHOC HeGOI s
(3BNQgG (B:s
(3gPG GdfHGJ eYQha HgPG GdGSe HGdOjGQ GdeUQjI hGdShGMd GdTGejI CjVkG hEPG UfY ef bTQ CZUGfg aJdkG hOSJ ai GdLQGMGJ hGdNfGRjQ s
(3LRA efg HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(4551) s
Keywords: (3GdWHs